Optimising the late-stage rehabilitation and return-to-sport training and testing process after ACL reconstruction - Buckthorpe, M. (Sports Medicine, 2019)
Despite increased knowledge on anterior cruciate ligament (ACL) injury mechanisms, improved surgical techniques, improved understanding of ACL biomechanics and enhanced knowledge in rehabilitation practice, return-to-sport (RTS) rates and subsequent second ACL re-injury rates after ACL reconstruction are not optimal. This narrative review discusses factors that may be highly relevant for RTS training and testing after ACL reconstruction, but which have received limited research attention to date or do not form part of the standard approach to rehabilitation. These factors include (1) explosive neuromuscular performance; (2) movement quality deficits associated with re-injury risk, particularly the need to re-train optimal sport-specific movement patterns; (3) the influence of fatigue; and (4) a lack of sport-specific re-training prior to RTS, with particular attention to an insufficient development of chronic training load. In addition, incorporating performance re-training and ensuring an athlete has restored their sport-specific profile is important. The relevance of these variables for RTS training and testing is discussed, with a new recommended model of late-stage rehabilitation and RTS training presented. Additional testing to support RTS decision making is also presented. This paper contains important information for practitioners and researchers to support optimised late-stage rehabilitation and RTS programmes and RTS testing with a view to enhancing patient outcomes after ACL reconstruction.